2017
DOI: 10.3748/wjg.v23.i29.5345
|View full text |Cite
|
Sign up to set email alerts
|

PBX1 attributes as a determinant of connexin 32 downregulation inHelicobacter pylori-related gastric carcinogenesis

Abstract: AIMTo clarify the mechanisms of connexin 32 (Cx32) downregulation by potential transcriptional factors (TFs) in Helicobacter pylori (H. pylori)-associated gastric carcinogenesis.METHODSApproximately 25 specimens at each developmental stage of gastric carcinogenesis [non-atrophic gastritis, chronic atrophic gastritis, intestinal metaplasia, dysplasia and gastric carcinoma (GC)] with H. pylori infection [H. pylori (+)] and 25 normal gastric mucosa (NGM) without H. pylori infection [H. pylori (-)] were collected.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Consistent with this, several studies on the gene expression profiles stimulated with H. pylori used human gastric cancer cell line but not human normal gastric epithelial cell line [26][27][28], and BGC823 cell line were frequently used to study the H. pylori related gastric carcinogenesis and related disease [29][30][31]. Since there were still no specific cell line to study the H. pylori related MALT lymphoma, in this study, we selected BGC823 cell line for further analysis to get as much information as possible.…”
mentioning
confidence: 72%
“…Consistent with this, several studies on the gene expression profiles stimulated with H. pylori used human gastric cancer cell line but not human normal gastric epithelial cell line [26][27][28], and BGC823 cell line were frequently used to study the H. pylori related gastric carcinogenesis and related disease [29][30][31]. Since there were still no specific cell line to study the H. pylori related MALT lymphoma, in this study, we selected BGC823 cell line for further analysis to get as much information as possible.…”
mentioning
confidence: 72%
“…The association between pre-B-cell leukemia transcription factor homeobox (PBX) with PBX1-4 in human and H. pylori is of interest: H. pylori increases the transcriptional factor PBX1 followed by downregulation of connexin 32 (Cx32) [55]. Decreased Cx32 is correlated with "the degree of tumor cell differentiation with unrestricted growth control" ( [56] reviewed in [55]).…”
Section: Pathogenic Stimulusmentioning
confidence: 99%
“…A previous study reported that the expression levels of Cx32 and Cx43 mRNA decreased gradually during H. pylori -associated gastric carcinogenesis, and this result is associated with the hypermethylation of the promoters of these genes[76]. H. pylori infection may upregulate some transcription factors, such as GATA-3[77] and PBX-1[58]. These transcription factors can serve as the determinants in the Cx32 promoter targeting site and thereby inhibit Cx32 expression.…”
Section: Cx32mentioning
confidence: 99%
“…Gastric tissue mainly produces Cx26, Cx32, Cx37, Cx40, Cx43, and Cx45[49-57]. Previous studies have shown that, compared to tissues or cells of the normal gastric mucosa, the expression of Cxs dramatically decreases in GC[58-61]. Therefore, the variations in Cxs can serve as important biomarkers that imply the development of different cancers.…”
Section: Introductionmentioning
confidence: 99%